Pengaruh kepemimpinan dan motivasi kerja terhadap kinerja karyawan (quality control epson 2) di PT Indonesia Epson Industry - Alviyandi; Isyanto, Puji (Relawan Sosial Ekonomi (RSE) Publisher, 2024)
This research aims to analyze the influence of leadership and work motivation on employee performance at PT Indonesia Epson Industry. By using transformational and transactional leadership theories as well as motivation theories such as Maslow's Hierarchy of Needs, McGregor's Theory X and Y, and McClelland's Theory of Needs, this research examines the interaction of these factors on employee performance. The research method uses multiple regression analysis with the T test and F test. The research population consists of 30 employees with a saturated sampling technique. Data was collected through a questionnaire that had been tested for validity and reliability. The research results show that leadership and work motivation have a significant effect on employee performance. An effective leadership style and appropriate work motivation improve employee performance. The T test shows a significant influence of individual variables, while the F test shows significant differences in performance based on variations in leadership style and work motivation. This research provides an understanding of the importance of the role of leadership and motivation in improving employee performance and its implications for the development of management strategies at PT Indonesia Epson Industry.